Production of xylanase by Aspergillus niger ATCC 16404 using oil palm leaf as substrate / Norazlina Idris - Idris, Norazlina (Institute of Graduate Studies, UiTM, 2016)
Malaysia generates agricultural wastes (agro-wastes) with the volume nearly 5 million tonnes yearly. At present, oil palm fronds are the major composition of agricultural waste materials that are exported to European countries for the industrial needs. Automatically, there is also a lot of oil palm leaf that was thrown away without being utilized. Oil palm leaf (OPL) was exploited as substrates for the cultivation of Aspergillus niger ATCC 16404 for the production of xylanase via solid state fermentation (SSF). SSF is generally defined as the growth of the microorganisms on solid material in the absence or near absence of free water. Five fermentation parameters were investigated in determining the most influential factors in maximizing the xylanase activity and via the five-factor two-level factorial design (statistical experiment design), only ratio of carbon and nitrogen, fermentation temperature and fermentation time were significant…